2013
DOI: 10.1111/j.1600-6143.2012.04316.x
|View full text |Cite
|
Sign up to set email alerts
|

Targeting TIM-1 on CD4 T Cells Depresses Macrophage Activation and Overcomes Ischemia-Reperfusion Injury in Mouse Orthotopic Liver Transplantation

Abstract: Hepatic injury due to cold storage followed by reperfusion remains a major cause of morbidity and mortality after orthotopic liver transplantation (OLT). CD4 T cell TIM-1 signaling co-stimulates a variety of immune responses in allograft recipients. This study analyzes mechanisms by which TIM-1 affects liver ischemia-reperfusion injury (IRI) in a murine model of prolonged cold storage followed by OLT. Livers from C57BL/6 mice, preserved at 4°C in UW solution for 20h, were transplanted to syngeneic recipients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 36 publications
3
29
0
Order By: Relevance
“…Furthermore, the expression of IFN-γ was depressed in TIM-3Tg recipients, along with enhanced GATA-3, IL-4, and IL-10 mRNA levels. A similar Th2-type polarization, with inhibition of Th1/Th17 cytokine programs was detected in liver IRI after TIM-1 blockade [19]. Thus, our findings are in agreement with the immunomodulatory role of TIM-targeted T cell differentiation/function in the early IRI phase in OLT recipients.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Furthermore, the expression of IFN-γ was depressed in TIM-3Tg recipients, along with enhanced GATA-3, IL-4, and IL-10 mRNA levels. A similar Th2-type polarization, with inhibition of Th1/Th17 cytokine programs was detected in liver IRI after TIM-1 blockade [19]. Thus, our findings are in agreement with the immunomodulatory role of TIM-targeted T cell differentiation/function in the early IRI phase in OLT recipients.…”
Section: Discussionsupporting
confidence: 89%
“…To further elucidate the role of CD4+ T cell-dependent TIM-3 immunomodulation, we used a model of liver IRI in RAG −/− mice [19]. Indeed, adoptive transfer of spleen CD4+ T cells (5×10 6 i.v.)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human TIM gene family, which contains TIM1, TIM3 and TIM4, is located on chromosome 5q23-35, a region that has been repeatedly linked with immune dysfunction, which may subsequently lead to autoimmune diseases, allergic diseases, chronic viral infections, immune rejections, and tumors. 10,11,15) The TIM1 gene, also known as hepatitis A virus cellular receptor 1 (HAVCR1) or kidney injury molecule 1 (KIM1), is a vital causative agent of immunological injuries and inflammatory disorders. Previous studies have demonstrated that transient over-expression of TIM1 or cross-linking TIM-1 with agonistic antibodies, in conjunction with T cell receptor (TCR) signal complex and CD28 stimulation, enhances T cell proliferation and cytokine production, which associates with various inflammatory disorders.…”
Section: Discussionmentioning
confidence: 99%